THE EFFECT OF SAP CONCENTRATION OF ARENG PALM (Arenga pinnata) ON SURVIVAL AND GROWTH OF MILKFISH (Chanos chanos Forskal) LARVAE - Gusmi, Diaz Asa; Diniarti, Nanda; Mukhlis, Alis (Jurnal Perikanan Unram, 2020)
The aims of the study were to determine the effect of sap concentration of areng palm (Arenga pinnata) on the survival and growth of milkfish larvae (Chanos chanos Forskal) and to get the best sap concentration for the survival and growth of milkfish larvae. The study used an experimental method and the experimental units randomized using a Completely Randomized Design (CRD) consisting of four treatments and each treatment was repeated three times. The treatments tested were the addition of areng palm sap into larval rearing media with a concentration of 2.4 ml/l, 4.8 ml/l and 7.2 ml/l. The treatment without adding areng palm sap was used as a control. This research was conducted at the Marine Aquaculture Development Center, Sekotong, West Lombok Regency, West Nusa Tenggara Province for 30 days starting from 31 August 2019 - 24 September 2019. The results showed that the addition of areng palm sap into the milkfish larvae rearing media had a significant effect in the survival and growth of milkfish larvae (F-value > Fcrit 5%). Larval survival, daily specific growth rate of body weight and absolute growth of the larval total length were obtained in the treatment of 7.2 ml/l with the value of each parameter is 67.85%, 15.25% per day and 9.05 mm for 18 days of maintenance. The three parameters in this concentration treatment did not show any significant difference with the treatment of 4.8 ml/l and 2.4 ml/l of areng palm sap concentration but were significantly different to the control treatment (0 ml/l). It is recommended to apply the addition of areng palm sap in the maintenance media of milkfish larvae with a maximum concentration of 7.2 ml/l. Further research needs to be done about increasing the concentration of areng palm sap above 7.2 ml/l in the media of milkfish larvae maintenance to get the optimum concentration for the survival and growth of milkfish larvae.